(untitled) (Universal International Scientific Journal, 2026)
This article scientifically covers the issue of improving the technical and tactical actions of 10-12 year old freestyle wrestlers during training. During the study, combination methods, situational sparring, exercises based on game elements, and video analysis methods were used. The results of pedagogical experience have shown that integrating technical and tactical tasks in a systematic approach to the training process significantly increases the athletes’ technical accuracy, ability to make quick decisions, and effectiveness in competitions. The comprehensive development of technical and tactical training in the 10-12 year old age period creates a solid foundation for high sportsmanship